Investigation of the effect of phosphoric acid (H3PO4) on rate of oil and solid separation in palm oil mill clarifier - Wong, Florence; Yong, S. (Springer Science, 2013)
In recent years, there is a growing demand for palm oil which is driven by the increase in human population and biodiesel production. In the palm oil milling process, a large quantity of water is consumed for the oil extraction process and consequently a large amount of wastewater is generated which is termed as palm oil mill effluent (POME). POME is a liquid waste having a high content of Biochemical Oxygen Demand (BOD) that deteriorates the quality of river water and pollutes the environment. Despite the development of various treatment systems to recover the water, a reduction in the production of this wastewater is still the best choice. This research seeks to improve the rate of separation of oil and solid in the clarifier mixture (CM) to improve the rate of oil recovery which will lead to a reduction in waste water generation and faster water recovery. Experiments were carried out to investigate the effect of dilution at 0, 80:20, 70:30, 60:40 clarifier mixture-water ratios, operating temperature at 70°C, 80°C, 90°C, and phosphoric acid application of 0%, 0.1%, 0.3%, 0.5% on the rate of separation. The results revealed that the best rate of oil flotation could be obtained at a temperature of 90°C with the treatment of 0.3% H3PO4 in the undiluted clarifier mixture. The addition of H3PO4 could neutralize the negative charges of oil by the introduction of positively charged hydrogen ions to enhance the coalescences of oil droplets. It could also induce the degumming process that could remove the emulsifying components of palm oil such as phosphatide. This could lead to a higher rate of solid and oil separation because when the emulsion was broken, oil density was reduced and the viscosity of the CM was reduced.